2019
DOI: 10.21273/horttech04293-19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Fertilizer Source and Rate on Growth and Nutrient Leachate Profile of Greenhouse-grown Cucumber

Abstract: Fertility management of seedlings and transplants is considered a key challenge in organic greenhouse production. This study was conducted to determine response of greenhouse-grown cucumber (Cucumis sativus) and nutrient release profile to two organic fertilizers and their combinations applied at three different concentrations in organic substrate. The organic fertilizers used were a turkey litter–based compost (TC) and a dairy manure vermicompost (VC). In addition, two contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Various reports have demonstrated a significant increment in the vegetative growth traits when investigating the effect of organic and biofertilizers on the growth and development of different crops [ 23 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In the present study, the results revealed that treatments T4 (rock phosphate (RP) + strain HM3) indicated the highest and most positive significant values for plant height, number of leaves per plant, and root length ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various reports have demonstrated a significant increment in the vegetative growth traits when investigating the effect of organic and biofertilizers on the growth and development of different crops [ 23 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In the present study, the results revealed that treatments T4 (rock phosphate (RP) + strain HM3) indicated the highest and most positive significant values for plant height, number of leaves per plant, and root length ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, buffalo dung was also used as compost fertilizer [11]. The use of dairy-based vermicompost had been reported to increase the growth of greenhouse cucumber [12] and potato [13]. Chicken manure has been widely reported to increase the yield of several vegetables, such as sweet corn [14], komatsuna [15], and kale [16].…”
Section: Introductionmentioning
confidence: 99%
“…Producers of organic tomato transplants, in particular, need to have reliable protocols for culturing robust and consistent transplant material for a variety of potential grower situations (Peet et al, 2008). However, fertility requirements and fertilization protocols for consistent production of high-quality organic transplants have not yet been determined (Li and Mattson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Transplant production is likely to become more important as demand for locally grown food increases, since it could enable small and mid-size farms to produce and harvest more uniform produce (Dufault, 1998). However, both supply and quality of transplants may be inadequate to support expansion of local production (e.g., Diaz-Perez et al 2008), and questions remain about fertility requirements to produce the best-quality seedlings and transplants (Li and Mattson, 2019). This uncertainty is especially true for organic transplants (Nair et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation